2012
DOI: 10.3892/ijmm.2012.1048
|View full text |Cite
|
Sign up to set email alerts
|

A novel mutation of exon 7 in growth hormone receptor mRNA in a patient with growth hormone insensitivity syndrome and neurofibromatosis type I

Abstract: Growth hormone insensitivity syndrome (GHIS), a genetic disease characterized by growth retardation combined with high serum concentration of growth hormone (GH) and low insulin-like growth factor 1 (IGF-1) levels, can be caused by mutations in the GH receptor (GHR) gene. We investigated the molecular defects in the GHR gene in a patient with neurofibromatosis type 1 (NF-1). The patient, a 2-year-old boy with NF-1, was assessed on his short stature by auxological, biochemical and molecular studies. Height of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…There are very few cases reported in the literature with mRNA mutations without a gene variant detected during sequence analysis of DNA. Kang et al 10 reported a case with GH insensitivity syndrome and neurofibromatosis. They did not detect any germline mutation in the exons or the flanking regions of the patient's growth hormone receptor ( GHR ) gene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are very few cases reported in the literature with mRNA mutations without a gene variant detected during sequence analysis of DNA. Kang et al 10 reported a case with GH insensitivity syndrome and neurofibromatosis. They did not detect any germline mutation in the exons or the flanking regions of the patient's growth hormone receptor ( GHR ) gene.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in mRNA were reported in extremely rare cases with systemic lupus erythematosus (SLE), neurofibromatosis, and growth hormone (GH) deficiency. 10–12 In nearly all cases, there were no DNA mutations in the related gene, whereas there were some variants detected in mRNA sequencing. This is the first case with LC with a normal DNA sequence, including coding and flanking regions, in which an mRNA variant was detected.…”
mentioning
confidence: 99%
“…3 Schematic representation of reported variants in the GHR gene and the corresponding protein structure including the signal peptide, an extracellular domain consisting of two FN3 subdomains, a transmembrane domain, and an intracellular domain. The identified variant in this study was marked in red [ 2 – 6 , 8 , 12 , 13 , 15 , 17 19 , 21 , 23 , 26 29 , 31 , 34 , 36 , 37 , 43 , 47 , 48 , 50 , 51 , 54 56 , 58 60 , 64 , 65 , 68 70 , 72 – 74 ] …”
Section: Case Presentationmentioning
confidence: 93%
“…Finally, a deletion of 166 bases of exon 7 in the GHR mRNA was found in a patient affected by neurofibromatosis and concomitant short stature. This mutation resulted in the premature termination of the sequence and thus in a reduced GH-binding affinity to the GHR, hence determining growth failure ( 43 ).…”
Section: Growth Hormone Insensitivity (Ghi)mentioning
confidence: 99%